Beneath the Wine-Dark Sea: Marine Imagery and Artefacts from the Bronze Age Aegean - Saunders, Emma (Trinity College Dublin, 2007)
This project began as an attempt to explain why the Minoan islanders developed and nurtured this marine interest, while neighbouring island cultures did not. In order to understand the enduring popularity of the sea in Minoan art, it is necessary to examine the wider social and religious role of the sea in Bronze Age Crete. As an avid scuba diver, I am also eager to apply marine biological research to identify behavioural observations and to test the accuracy of the Minoan depictions of marine life. My main area of research concerns the role of marine imagery and artefacts in ritual and funerary contexts. By exploring the marine aspect of Minoan religious ritual, I have found that the Minoans frequently offered marine objects such as painted shells and model boats in their shrines, and many of these shrines have a direct visual relationship with the sea. The Minoans also used vessels decorated with marine imagery as well as real marine shells, such as the large triton shell, as cult equipment. Triton shells, for example, were modified for use as ritual trumpets and as libation vessels (for pouring liquid offerings). The marine world also extended to funerary contexts, where octopus cut-outs were often sewn to funerary shrouds and marine creatures such as octopi and giant fish were used to decorate coffins larnakes). One aspect of my project involves assessing the extent to which marine motifs found in funerary contexts may relate to complex funerary beliefs concerning regeneration, fertility and an afterworld located overseas. The sea, which was so omnipresent in Minoan art, also permeated every aspect of Minoan life and death. Contextual analysis of marine imagery and artefacts suggests that marine motifs were not only decorative but could act as multi-referential visual symbols, with a range of different associations which careful study can bring to light.
Exhibited at the second Glucksman Memorial Symposium on June 13th 2007
Keywords: Bronze Age Aegean; Marine imagery; Marine artefacts